Instructional Leadership Practices of School Principals in Remote Areas: A Multi-Site Study in South Central Timor Regency - Arifin; I Nyoman Jampel; Dewa Bagus Sanjaya; I Wayan Widiana (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2026)
Principal learning leadership is an important factor in improving the quality of education, but its implementation in remote areas still faces various structural and resource limitations. This study aims to describe the learning leadership practices of school principals in schools in remote areas of South Central Timor Regency, analyze adaptive strategies applied in managing learning in the midst of limitations, and formulate its conceptual contribution to the development of educational leadership theory. This study uses a qualitative approach with a multi-case study design in three schools. Data were collected through in-depth interviews with principals and teachers, observations, and documentation, then analyzed thematically to identify patterns of practice and leadership strategies. The results of the study show that learning leadership practices run in diverse and contextual forms. School principals continue to carry out the functions of supervision and management of learning, but their intensity and quality are influenced by personal capacity, structural support such as infrastructure and access to training, and government policies. Adaptive strategies that emerge include strengthening internal solidarity, self-training, and orientation to the sustainability of educational services in the midst of limitations. This study concludes that learning leadership in remote areas is adaptive and contextual, so its development needs to consider geographical, social, and structural factors to be in harmony with the reality of the field.